Краснозобая казарка (Rufibrenta ruficollis) на Украине - Лысенко, В.И. (Вестник зоологии, 1983)
According to palacontological data, the red-breathed goose was always a common migratory bird of the southern part of the Ukraine. Presently its flyway runs over the Northern part of Azov and Black seas. Migrating birds usually stop for a long time in Molochny and Utlyuksky estuaries, Eastern Sivash and Danube delta. The migration goes in long distance jumps, so that on most Azov and Black sea coast the bird still remains rare;